2007
DOI: 10.1111/j.1744-7917.2007.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of boll weevil (Coleoptera: Curculionidae) adults after feeding on pollens from various sources

Abstract: The survival of overwintering boll weevil, Anthonomus grandis grandis (Boheman), adults on non-cotton hosts in the Lower Rio Grande Valley (LRGV) of Texas was examined from 2001 to 2006. The success of the Boll Weevil Eradication Program, which was reintroduced into the LRGV in 2005, depends on controlling overwintering boll weevil populations. Laboratory studies were conducted using boll weevil adults that were captured in pheromone traps from September through March. The number of adults captured per trap de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 26 publications
0
16
0
1
Order By: Relevance
“…According to Ribeiro et al (2010), pollen from different plant species found in remnants of Cerrado vegetation is used by adult boll weevils during the intercrop period. Therefore, areas of natural vegetation, such as the Cerrado, may be sources of alternative food due to the diversity of plants, as can be the case with any environment, even a cultivated field, which provides alternative food, as found by Spurgeon & Raulston (2006), Showler (2006), and Greenberg et al (2007).…”
Section: Resultsmentioning
confidence: 99%
“…According to Ribeiro et al (2010), pollen from different plant species found in remnants of Cerrado vegetation is used by adult boll weevils during the intercrop period. Therefore, areas of natural vegetation, such as the Cerrado, may be sources of alternative food due to the diversity of plants, as can be the case with any environment, even a cultivated field, which provides alternative food, as found by Spurgeon & Raulston (2006), Showler (2006), and Greenberg et al (2007).…”
Section: Resultsmentioning
confidence: 99%
“…Sabe-se que durante a entressafra o inseto pode utilizar algumas estratégias de sobrevivência que possibilitam a manutenção de suas populações na safra seguinte, dentre elas a capacidade de se alimentar de pólen de muitas famílias de plantas, como relatado por diversos autores (CUADRADO e GARRALLA, 2000;CUADRADO, 2002;GABRIEL, 2002;GREENBERG et al, 2007;JONES, GREENBERG, EISCHEN, 2007;RIBEIRO et al, 2010).…”
Section: Introductionunclassified
“…The numbers of pollen grains recorded in the gut of H. axyridis were similar to or higher than those found in other beetle species that occasionally exploit pollen in the field. The western rootworm Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae) is reported to have 40 to 120 pollen grains in its gut (Moeser & Vidal, 2005) and the boll weevil Anthonomus grandis grandis (Boheman) (Coleoptera: Curculionidae) 2 to 25 pollen grains (Greenberg et al, 2007). The amount of pollen consumed by insects varies greatly among species depending on whether it is an essential food supporting development and/or reproduc-tion, as in female hoverflies (Hickman et al, 1995;Irvin et al, 1999), or merely a supplementary or alternative food sustaining survival for a short period of time, as in boll weevils (Greenberg et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The western rootworm Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae) is reported to have 40 to 120 pollen grains in its gut (Moeser & Vidal, 2005) and the boll weevil Anthonomus grandis grandis (Boheman) (Coleoptera: Curculionidae) 2 to 25 pollen grains (Greenberg et al, 2007). The amount of pollen consumed by insects varies greatly among species depending on whether it is an essential food supporting development and/or reproduc-tion, as in female hoverflies (Hickman et al, 1995;Irvin et al, 1999), or merely a supplementary or alternative food sustaining survival for a short period of time, as in boll weevils (Greenberg et al, 2007). In the present study, fertile H. axyridis adults fed in the laboratory on only ad libitum quantities of pollen had about 35000 pollen grains in their gut, indicating that the majority of field collected H. axyridis adults had only ingested small amounts of pollen and that it may only be a supplementary source of nutrients for this coccinellid.…”
Section: Discussionmentioning
confidence: 99%